Thermal management of solid state power switches - Tighe, Christopher James Frederick (2011)
The transient temperature of solid state power switches is investigated using thermal resistance network modelling and experimental testing. The ability of a heat sink mounted to the top of the device to reduce the transient temperature is assessed. Transient temperatures for heat pulses of up to 100ms are of most interest.